Rational Design of 2D Supramolecular Networks Switchable by External Electric Fields - Cometto, Fernando Pablo (2024)
The reversible formation of hydrogen bonds is a ubiquitous mechanism for controlling molecular assembly in biological systems. However, achieving predictable reversibility in artificial two-dimensional (2D) materials remains a significant challenge. Here, we use an external electric field (EEF) at the solid/liquid interface to trigger the switching of H-bond-linked 2D networks using a scanning tunneling microscope. Assisted by density functional theory and molecular dynamics simulations, we systematically vary the molecule-to-molecule interactions, i.e., the hydrogen-bonding strength, as well as the molecule-to-substrate interactions to analyze the EEF switching effect. By tuning the building block’s hydrogen-bonding ability (carboxylic acids vs aldehydes) and substrate nature and charge (graphite, graphene/Cu, graphene/SiO2), we induce or freeze the switching properties and control the final polymorphic output in the 2D network. Our results indicate that the switching ability is not inherent to any particular building block but instead relies on a synergistic combination of the relative adsorbate/adsorbate and absorbate/substrate energetic contributions under surface polarization. Furthermore, we describe the dynamics of the switching mechanism based on the rotation of carboxylic groups and proton exchange, which generate the polarizable species that are influenced by the EEF. This work provides insights into the design and control of reversible molecular assembly in 2D materials, with potential applications in a wide range of fields, including sensors and electronics.